Coping up mechanism and financial aid scheme for cancer treatment at a tertiary care hospital in Lucknow - Verma, Rahul; Ahmad, Naim; Singh, Vijay Kumar; Akhtar, Naseem (International Journal Of Community Medicine And Public Health, 2023)
Background: Cancer treatment has one of most expensive disease treatment due to its chronicity and expertise. In a region where per capita income of persons/ annual income of household is low, they have to depend on some coping up mechanism or financial aid schemes for successful completion of treatment. But awareness and proportion of utilization of the financial benefit for cancer patient is doubtful. The present study aims to study coping up mechanism and financial benefits availed by cancer patients at a tertiary care hospital in Lucknow. Methods: The study was done in a tertiary care hospital in Lucknow. 120 cancer patients who had undergone treatment and come for follow-up were taken from surgical oncology OPD. Data was collected using an interview-based pre-tested, self-administered questionnaire and analyzed using MS excel 2017 and SPSS v 23. Results: About 64 % of participants borrowed money from social net, 3% took loans, 10% mortgage assets, and 20% sold their assets to cope up with high expenditure on cancer treatment. Financial benefit of schemes was availed by about 1/3rd of participants and 20% availed concessions in rail/road travel fare and 16% availed concessions in income tax. Conclusions: Large number of people had to use some of the coping up mechanism for treatment of cancer this further pushes them into viscous cycle of poverty And at same time they are unable to avail benefits of financial aid schemes by government and others for cancer patients. Thus, an increase in utilization and coverage of government financial aids or insurance is needed.